2021
DOI: 10.1111/psyg.12762
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and factors related to life satisfaction in nursing home and community‐dwelling older adults during COVID‐19 pandemic in Turkey

Abstract: Background The geriatric population is supposed to be at high risk for psychological distress as well as adverse outcomes and mortality during the COVID‐19 pandemic. This study aimed to investigate the levels of depression, anxiety, death anxiety and life satisfaction levels and factors related to life satisfaction in individuals aged 65 years and older during the pandemic and to compare these variables between nursing home (NH) and community‐dwelling older adults. Method This study has a cross‐sectional and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…It has been recognized that COVID-19 measures have resulted in negative psychological and behavioral consequences for older adults with and without dementia [ 7 14 ]. Likewise, studies in long-term care settings have found increases in depression, anxiety, loneliness, and behavioral problems that were attributed to the COVID-19 restrictions [ 15 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized that COVID-19 measures have resulted in negative psychological and behavioral consequences for older adults with and without dementia [ 7 14 ]. Likewise, studies in long-term care settings have found increases in depression, anxiety, loneliness, and behavioral problems that were attributed to the COVID-19 restrictions [ 15 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The full text of all 33 remaining potentially eligible studies were retrieved, and 15 papers were excluded with reasons, leaving 18 studies included. The studies were published in a range of countries including: Spain (3) (Cortés Zamora et al, 2022; Pereiro et al, 2021; Pérez‐Rodríguez et al, 2021), Turkey (2) (Arpacıoğlu et al, 2021; Savci et al, 2021), United Kingdom (1) (Davies‐Abbott et al, 2021), New Zealand (1) (Cheung et al, 2021), Israel (1) (Ayalon & Avidor, 2021), France (1) (El Haj et al, 2020), China (1) (Ho et al, 2022), Switzerland (1) (Huber & Seifert, 2022), Canada (1) (Ickert et al, 2021), Belgium (1) (Kaelen et al, 2021), United States of America (1) (Levere et al, 2021), Sweden (1) (Lood et al, 2021), Ireland (1) (Murphy et al, 2022), Croatia (1) (Solić et al, 2021), and Thailand (1) (Srifuengfung et al, 2021). All studies were conducted during the COVID‐19 pandemic from early 2020 to mid‐2021.…”
Section: Resultsmentioning
confidence: 99%
“…It was common for residents to experience loneliness during the pandemic (Huber & Seifert, 2022) with moderate to severe negative impact on familial relationships (Arpacıoğlu et al, 2021; Savci et al, 2021; Srifuengfung et al, 2021). Many individuals started using modern forms of communication (such as FaceTime, Zoom, etc) to stay in social contact with others (Solić et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Former research has been demonstrated that individuals living in institutionalized settings generally score lower in various health-related factors [ 22 ] and also in psychosocial factors [ 23 ] such as satisfaction with life. Thus, an association between living arrangement and driving status is very plausible.…”
Section: Discussionmentioning
confidence: 99%